Tinjauan Literatur Tentang Penelitian Arus Kas di Indonesia Periode 2017-2019 - Fauziah Husain (STIE Kertanegara Malang, 2021)
The purpose of this study is to identify and classify research articles on cash flow that have been studied in Indonesia from 2017 - 2019. This research uses the literature review method by collecting and reviewing articles published in the Garuda Ristekdikti database journal in 2017- 2019 where “Cash Flow” was the keyword in article searches. This research can identify and classify the literature on cash flow research systematically so that it can provide an overview and overview of the studies that have been carried out and identify emerging research to be followed up in the future. The findings of the literature review on cash flow research are grouping articles of cash flow as many as 38, operating cash flow as much as 49, investment cash flow as much as 17, funding cash flow as much as 20, free cash flow as much as 15 and future cash flow as many as 13 articles. The classification shows that the cash flow variable and cash flow components can be connected with other independent variables as independent, dependent and intervening variables.